2017
DOI: 10.1093/ons/opx155
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgery Simulator of Cerebral Aneurysm Clipping with Interactive Cerebral Deformation Featuring a Virtual Arachnoid

Abstract: A virtual clipping simulator mainly focusing on supporting tissues and less on physical properties seemed to be useful in the surgical simulation of cerebral aneurysm clipping. To our knowledge, this article is the first to report brain deformation based on supporting tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…We try to follow guidelines for achieving efficient workflow in skill laboratories published elsewhere, [ 3 7 29 ] and training sessions are being organized in coordination with different other surgical subspecialities, for example, head-and-neck surgery, traumatology, surgical oncology, and urology for maximum utilization of resources (cadavers). We agree that advancements in virtual simulators are challenging the “Gold standard status” of cadaver training, [ 20 30 31 32 ] and there is a general sentiment that these are ultimately destined to replace the art of cadaveric dissection. Still, a high-quality virtual simulator, which has realistic deformation of tissues and a good haptic feedback, requires a heavy investment in terms of initial cost, and as of now, they are yet not freely available outside few institutes in the west.…”
Section: Discussionmentioning
confidence: 99%
“…We try to follow guidelines for achieving efficient workflow in skill laboratories published elsewhere, [ 3 7 29 ] and training sessions are being organized in coordination with different other surgical subspecialities, for example, head-and-neck surgery, traumatology, surgical oncology, and urology for maximum utilization of resources (cadavers). We agree that advancements in virtual simulators are challenging the “Gold standard status” of cadaver training, [ 20 30 31 32 ] and there is a general sentiment that these are ultimately destined to replace the art of cadaveric dissection. Still, a high-quality virtual simulator, which has realistic deformation of tissues and a good haptic feedback, requires a heavy investment in terms of initial cost, and as of now, they are yet not freely available outside few institutes in the west.…”
Section: Discussionmentioning
confidence: 99%
“…e treatment of cerebral aneurysm is a very complicated process, and accurate diagnosis of the patient is a critical step [11]. e patient's diagnosis rate is closely related to the quality of the examination images.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical simulation is not novel and is greatly accepted for training residents or improving specific surgical skills, only a few studies have been reported that involved rehearsing a patient's cerebrovascular lesion operation before the actual surgery (Table 2). In fact, the majority of these studies have compared the preplanned procedure to the actual surgery for aneurysm clip- Similar strategy performed in the actual surgery; strategy (e.g., more clips) usually changed because of hard wall or wide-necked lesion ping 7,9,10,19,21,22 and endovascular management; these studies have mainly assessed microcatheter vascular access or endosaccular embolization. 6,8,13 In general, the results of the above studies suggest that the preplanned strategy is usually performed in the actual procedure and the benefits are perceived by the operator, however, there is no consensus on how to objectively measure outcomes after simulation and there is no prediction of the long-term outcome for the patient.…”
Section: Discussionmentioning
confidence: 99%